Writing Jazz History: The Emergence of a New Genre - Dunkel, Mario (Current Objectives of Postgraduate American Studies, 2012)
While very early jazz criticism was often limited to the form of journal articles, music critics in the 1930s started to publish longer books on the music and—as I will argue in my paper—created a new genre: the jazz history.